Child protection and family support practice in Ireland: a contribution to present debates from a historical perspective. Issue 3 (16th December 2016) - Devaney, Carmel; Gregor, Caroline Mc
Abstract: This paper takes the opportunity of the current child welfare system change in Ireland to promote the value of learning from history to better understand the interface between family support and child protection. The paper draws from the histories of child protection and family support to illuminate the commonalities and differences that have come to define the two practices. Using findings from two historical studies – one on family support and the other on child protection – the paper demonstrates the unique features and the many integrated elements of family support and child protection in Ireland. It is argued that students and practitioners need to be provided with a stronger sense of the historical developments that have shaped the present. This will enable comprehension of the complex context within which current relations between 'protection' and 'support' are negotiated and help to avoid operating in a vacuum of a present only viewpoint. The paper concludes with reference to the need for students and practitioners to navigate the complex relationship between family support and child protection at practice, policy and organizational level through a well‐informed knowledge of the historical as well as the present context.